Testing of Micro Switches for Garden Tools - Sipkás, Vivien; Bodnár, Gabriella (International Journal of Engineering and Management Sciences, 2019)
The aim of this paper is to introduce the design of testing method for the prediction of the life and acceleration methods of the micro switches applied in different type of garden tools. These products will be tested for complex stressing, for example higher temperature, humidity, current load and so on. Therefore, the most important information and multi-factor acceleration models are summarized, the Weibull, the lognormal and the exponential distributions which are suitable for performing and evaluating tests.